Teaching English Pronunciation Using Tongue Twister - Prasetyawan Aji Sugiharto; Yan Imam Santoso; Maila Huda Shofyana (Universitas Muhammadiyah Kalimantan Timur, 2022)
This study was aim to know how tongue twister can enhance students’ pronunciation ability at the first semester English Education Study Program STKIP Muhammadiyah Batang in academic year 2021/2022. This study conducted at the first semester of English Education study program that consist of 35 students as sample. This is a quantitative research. The researcher uses pre-experimental design using “one-group pretest-posttest design. The researcher uses pre-test and post-test to collect the data. Based on the calculation, the result of t-value is 3.965. In addition, the result on the mean score of post-test is higher than the mean score of pre-test (70.71>64.28). Then, the researcher consults the critical value to the t-table using the 5% (0.05) alpha level significance and the degree of freedom is 1.67. It shows that the t-value is higher than t-table (3.965>1.67). It means that Tongue Twister is effective to enhance students’ pronunciation ability for the first semester students of English Education Study Program STKIP Muhammadiyah Batang. The use of tongue twister make student more active and their pronunciation ability was improved.